2000
DOI: 10.1081/ddc-100101318
|View full text |Cite
|
Sign up to set email alerts
|

Potential Applications of Carbomer in Oral Mucoadhesive Controlled Drug Delivery System: A Review

Abstract: Carbomers are extensively being used in controlled drug delivery systems (CDDS). They are also finding numerous applications in oral mucoadhesive drug delivery because of their ability to interact with the mucus glycoprotein and to remain localized to a specific site. The present review aims at giving an insight into the potential application of carbomers in mucoadhesive CDDS. This review deals with the physicochemical properties of carbomers and various mechanisms of mucoadhesion. The mechanism for the releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(98 citation statements)
references
References 79 publications
3
93
0
2
Order By: Relevance
“…Figure 3 shows that, at the same concentration of CP 974P (0.3% or 0.4%), viscosity of the complex solution is much higher than that of carbopol solution. It is known that viscosity of acid carbopol solution can increase when neutralized (Singla et al, 2000), so the increase in viscosity demonstrated carboxyl groups of carbopol have been partly or totally neutralized, which may have resulted from the interaction between carbopol and ATM.…”
Section: Rheological Studiesmentioning
confidence: 99%
“…Figure 3 shows that, at the same concentration of CP 974P (0.3% or 0.4%), viscosity of the complex solution is much higher than that of carbopol solution. It is known that viscosity of acid carbopol solution can increase when neutralized (Singla et al, 2000), so the increase in viscosity demonstrated carboxyl groups of carbopol have been partly or totally neutralized, which may have resulted from the interaction between carbopol and ATM.…”
Section: Rheological Studiesmentioning
confidence: 99%
“…Mucoadhesive nanoparticulate systems such as polymercoated liposomes were found to be useful carriers for improved oral delivery because of their prolonged retention in the GI tract and excellent penetration into the mucus layer 5 . The mucoadhesive liposomes can be prepared by coating drug carrier surface by various mucoadhesive polymers such as chitosan [10][11][12][13] , Carbopol 9,14,15 , and Eudragit…”
Section: Introductionmentioning
confidence: 99%
“…Its mucoadhesive properties are due to the molecular attractive forces formed by the electrostatic interaction between positively charged chitosan and negatively charged mucosal surfaces 17,18 . Carbopol polymers are polymers of acrylic acid cross-linked with polyalkenyl ethers or divinyl glycol and they are also finding numerous applications in oral mucoadhesive drug delivery because of their ability to interact with the mucus glycoprotein and to remain localized to a specific site 14,15,19 . Polymethacrylates for pharmaceutical purposes became known under the trademark Eudragit.…”
mentioning
confidence: 99%
“…This work focuses on the development of an inexpensive vaginal gel formulation for the sustained delivery of PYD using GRAS (generally regarded as safe) ingredients-polyacrylic acid (PAA) and a cellulose derivative (15,27,34,38). In particular, hydroxylethyl cellulose (HEC) has been used in several vaginal gel formulations, including the universal placebo gel (32).…”
mentioning
confidence: 99%